O Ser e seus significados em Aristóteles - Silva, George Carlos da (2022)
This dissertation aims to analyze the doctrine of being and its meanings in Aristotle. According to him, the question about what being is has always been present as an object of investigation among ancient thinkers, who differed as to its nature, unity and diversity. Heir to this tradition, Aristotle sought to develop a science of being as being and of its essential attributes and, in this way, elaborated a doctrine that has as its starting point the identification of the various ways of saying being. In this work, we seek to cover the course of these meanings, among them: the accident, the potency and the act, the truth and the substance (ousia), which was understood by Aristotle as a privileged and first being.